Writing About Literature: Essay and Translation Skills for University Students of English and Foreign Literature, 1st edition - Woolf, Judith (Routledge, 2020)
Writing about Literature combines detailed practical and scholarly advice with a sense of the scope and creative possibilities of literary criticism, empowering the student reader to make his or her own discoveries and experiments with language. In addition, it gives valuable guidance on adult language learning and translation skills for students of foreign literature.